Metabolomics Analysis of Morchella sp. From Different Geographical Origins of China Using UPLC-Q-TOF-MS - Dong, Hui; Zhao, Xiaoyan; Cai, Min; Gu, Haotian; E, Hengchao; Li, Xiaobei; Zhang, Yanmei; Lu, Huan; Zhou, Changyan (Frontiers in Nutrition, 2022)
The morel mushroom (Morchella sp.) is recognized as one of the most highly-prized edible fungi with a ceaseless expansion of cultivated area as well as its commercial popularity in China. However, methods that can evaluate the quality and the levels of chemical constituents in morels from different geographical origins are rarely reported. In this study, an untargeted UPLC-Q-TOF-MS-based metabolomics approach was conducted to study the metabolite profiles of morel samples from four different geographical origins of China, including Gansu, Guizhou, Liaoning, and Henan province. Multivariate analysis was performed to further differentiate the morels from different geographical origins. 32 differential metabolites involving lipids, organic acids, amino acids and ketones were identified to distinguish the morel samples from different regions. Furthermore, the KEGG metabolic pathway analysis demonstrated that lipid metabolism and amino acid metabolism were intimately interwoven with geographical origin. Based on the results of this study, it is concluded that metabolomics provides new insights into tracing and authenticating subtle differences of samples from different geographical origins efficiently, and conducting the preliminary quality evaluation of samples